Hannah Arendt on Truth and Public Honor: Why Judgment and Forgiveness Require Civic Pedagogy: Hanah Arendt, Kebenaran dan Penghormatan Publik. Mengapa Pertimbangan dan Pengampunan Membutuhkan Pedagogi - Fransiskus Sule; Hector Guazon (STF Driyarkara - Diskursus, 2026)
This article addresses the question what becomes of a common world when the state bestows public honor amid unresolved authoritarian harm and contested facts, focusing on Indonesia’s 2025 designation of former President Soeharto as pahlawan nasional (national hero). Using an interpretive qualitative design grounded in document analysis of official statements, civic testimony, and public commentary, and informed by Hannah Arendt’s accounts of factual truth, judgment, punishment, and forgiveness, the article clarifies the political stakes of hero-making in a post-authoritarian public sphere. It argues, first, that factual truth is politically vulnerable and requires witnesses and institutions if it is to remain publicly binding; where those supports fail, honor can function as organized forgetting. Second, public honor is not an extension of private affection but a judgment that must remain communicable and contestable in plural public sphere, rather than enforced through “lovers versus haters” pressure. Third, forgiveness, in Arendt’s sense, interrupts retaliation but presupposes truth and responsibility; without accountability, “forgive and forget” becomes a technology of impunity. The article concludes by outlining a civic pedagogy of counter-memory and enlarged judgment after honor has been conferred. Keywords: Hannah Arendt, factual truth, public judgment, forgiveness, public honor, defactualization Abstrak Artikel ini menyoroti penetapan mantan Presiden Soeharto sebagai pahlawan nasional pada 2025 dan mempertanyakan apa yang terjadi pada dunia-bersama ketika negara menganugerahkan kehormatan publik di tengah luka otoritarian yang belum terselesaikan dan fakta yang kebenarannya masih diperdebatkan. Menggunakan desain kualitatif interpretatif, yakni analisis dokumen atas pernyataan resmi, kesaksian warga, dan komentar publik, yang dibaca melalui uraian Hannah Arendt tentang kebenaran faktual, penilaian Kantian, dan pengampunan/hukuman, artikel ini mengklarifikasi pertaruhan politik dari pengangkatan pahlawan di ruang publik pasca-otoritarianisme. Pertama, kebenaran faktual rentan secara politis dan memerlukan saksi serta institusi agar tetap mengikat secara publik; tanpa itu, kehormatan dapat berfungsi sebagai “pelupaan yang terorganisir.” Kedua, kehormatan publik bukan perpanjangan dari kasih saying pribadi tetapi penilaian yang harus dapat dikomunikasikan dan diperdebatkan dalam kemajemukan, daripada ditegakkan lewat dikotomi “pencinta vs pembenci.” Ketiga, pengampunan Arendtian memutus rantai balas-dendam, tetapi mengandaikan kebenaran dan tanggung jawab; tanpa akuntabilitas, “maafkan dan lupakan” menjadi teknologi impunitas. Artikel diakhiri dengan menguraikan pedagogi kewarganegaraan berupa kontra-memori dan penilaian yang diperluas setelah kehormatan dianugerahkan. Kata-kata Kunci: Arendt, kebenaran faktual, penilaian publik, pengampunan, kehormatan publik, defaktualisasi